An Audit of Intensive Care Services in Bangladesh - Faruq, Mohammad Omar; Ahsan, ASM Areef; Fatema, Kaniz; Ahmed, Fatema; Sultana, Afreen; Chowdhury, Rashed Hossain (Ibrahim Medical College Journal, 2010)
This study was conducted to survey the facilities, bed strength, functional characteristics, manpower, operational practices and distribution of intensive care units in Bangladesh. Direct interview of consultants in charge of different Intensive Care Units (ICUs) in the city of Dhaka was conducted by a structured questionnaire. All Adult Intensive Care Units (ICUs) and Coronary Care Units (CCUs) with ventilator support in the city of Dhaka belonging to government and private sectors were included. Our survey showed that 90% of all Intensive Care Units in Bangladesh were located in the city of Dhaka. There were 40 Intensive Care Units in the city of Dhaka, of which 33 were ICUs and 7 CCUs with ventilator support (also considered as ICU). Only 4 (10%) ICUs were located in government hospitals. Rest of the ICUs was in private hospitals / clinics. Total number of ICU beds was 424 and total numbers of beds in these hospitals were 8824. So 4.8% of total hospital beds were provisioned for critical care. Among these only 240 beds (60%) had ventilator support. 27(68%) of the 40 ICUs were multidisciplinary, 7(18%) CCUs, 5(12%) cardiac surgery and 1(2%) neurology. 64% ICUs were run by anesthesiologists. 85% facilities were open units as opposed to 15% closed units. Nurse: bed ratio of 1:1 was seen in 15(42%) facilities. On duty doctor: patient ratio was variable and highest was 1:4 in 9 ICUs (27 %). ICUs in Bangladesh are mainly situated in the city of Dhaka and mostly in the private sector. The standards and management strategies vary greatly. Ibrahim Med. Coll. J. 2010; 4(1): 13-16 Key words: Intensive Care Unit; Bangladesh; audit. DOI: 10.3329/imcj.v4i1.5929